Застосування спектрального аналізу вимови голосних для прогнозування динаміки нейром'язових стенозів гортані у ранній поопераційний період - Паламарчук, В. А. (Clinical Endocrinology and Endocrine Surgery, 2009)
On the basis of computer program TrueRTA (Real Tiam Audio Spectrum Analyzer by J.L.Murphy) for research of parametres of a voice the voice spectral analysis of patients who have a surgical pathology of a thyroid gland on pre and postoperative stages was investigated. Possibility of application of this method for an estimation of reversibility of postoperative neuromuscular laryngeal stenosis was shown. Criteria of reversibility are the typical form of the enveloping spectrogram, frequency characteristics and a correlation of amplitudes of energy extremums of vowel sounds (a phoneme "i:" in a slavic transcription).